Before and After the Pandemic: Alcohol Consumption and Related Problems in Argentina - Conde, Karina; Gimenez, Paula Victoria; Salomón, Tomás; Peltzer, Raquel Inés; Laspiur, Sebastián; Cremonte, Mariana (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The impact of the COVID-19 pandemic and isolation measures on alcohol consumption remains unknown among Latin-American countries. This paper characterizes differences in alcohol consumption and related problems before and after the pandemic among Argentinians from different genders, age groups, income levels, and behaviors regarding the acquisition of alcoholic beverages. Through an online survey 1446 participants were assessed regarding four alcohol consumption dimensions (frequency, quantity, heavy episodic drinking -HED- and alcohol-related problems) three months prior and after the first cases in the country and subsequent lockdown measures. Overall, participants reported small reductions for usual consumption and moderate ones for HED and related problems. As expected, very high reductions were found for those underage (14 to 18 years), and young adults (19 to 24 years). Those who had an increase in income after the pandemic did not report changes in consumption, while those whose income remained equal or lowered reported reductions. Those who did not report special behaviors to acquire alcohol (e.g. pre-stocking) informed decreases in consumption compared to those who did. This study provides new evidence on the impact of environmental factors in public health, suggesting restricted access to alcohol generates a significant decrease in alcohol consumption and related problems.